Reflections on the Triptych of Meristems That Build Flowering Branches in Tomato - Périlleux, Claire; Huerga-Fernández, Samuel (Frontiers in Plant Science, 2022)
Branching is an important component determining crop yield. In tomato, the sympodial pattern of shoot and inflorescence branching is initiated at floral transition and involves the precise regulation of three very close meristems: i) the shoot apical meristem (SAM) that undergoes the first transition to flower meristem (FM) fate, ii) the inflorescence sympodial meristem (SIM) that emerges on its flank and remains transiently indeterminate to continue flower initiation, and iii) the shoot sympodial meristem (SYM), which is initiated at the axil of the youngest leaf primordium and takes over shoot growth before forming itself the next inflorescence. The proper fate of each type of meristems involves the spatiotemporal regulation of FM genes, since they all eventually terminate in a flower, but also the transient repression of other fates since conversions are observed in different mutants. In this paper, we summarize the current knowledge about the genetic determinants of meristem fate in tomato and share the reflections that led us to identify sepal and flower abscission zone initiation as a critical stage of FM development that affects the branching of the inflorescence.